FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI DI KECAMATAN KALIANDA, LAMPUNG SELATAN - YH, Aryan Ari Sepri; Harlianda, Triyandita Kusuma; Safitri, Anggun (Agripreneur : Jurnal Pertanian Agribisnis, 2025)
Rice plays an important role as a staple food for majority of the population, making the increase in rice production a crucial factor. There are many factors that can increase rice production, including natural resources, technology, and environmental conditions. The purpose of this study is to explain the factors that influence rice production. The research was conducted in Kalianda District, South Lampung, with a sample size of 80 respondents and the data collection period was from February to March 2025. The data were analyzed using multiple regression with the Ordinary Least Squares (OLS) method through the SPSS application, followed by classical assumption testing and statistical tests. The results of the study show that the adjusted R² value obtained was 0.924 or 92.4%. The calculated F-value was 74.038, indicating that all independent variables significantly influence the dependent variable. The factors affecting rice production in Kalianda District, South Lampung are land area and the age of farmers.